India and the Multilateral Trading System after Seattle : Toward a Proactive Role - Mattoo, Aaditya (World Bank, Washington, DC, 2015)
The authors argue that India should engage more actively in the multilateral trading system for four reasons: First, such engagement could facilitate domestic reform, and improve access to export markets. If the government could show that domestic reform would pay off with increased access to markets abroad, those who gain from such access - whether they export textiles, software, professional services, or other products - could represent a countervailing voice to reform's opponents. In turn, the need for this external payoff to secure domestic reform makes India a credible bargainer, which could induce trading partners, to open their markets to India. Second, external commitments can foster good domestic policies, by providing guarantees against the reversal of current policies, or lending credibility to promises of future reform. Such pre-commitments could help strike a balance between the reluctance to unleash competition immediately, and the desire not to be held perpetual hostage to vested interests, or weak domestic industries. Third, engagement can help enforce India's market access rights. If other countries do not eliminate quotas on textiles, and clothing as scheduled, India can credibly threaten to withdraw its obligations under the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPs). Fourth, multilateral tariff reduction could reduce the disadvantage (to India) of not being part of regional agreements. The value of multilateral engagement might be limited, if the prospects for securing increased market access are dim, as the failed Seattle negotiations might appear to suggest. India must credibly test negotiating pessimism by showing its willingness to open its markets in return for improved access to foreign markets. Success is not certain, but India's chances are improved if aligns itself with countries pressing for sound policies of open trade.